2018
DOI: 10.1044/2018_jslhr-h-17-0233
|View full text |Cite
|
Sign up to set email alerts
|

Basic Measures of Prosody in Spontaneous Speech of Children With Early and Late Cochlear Implantation

Abstract: Purpose Relative to normally hearing (NH) peers, the speech of children with cochlear implants (CIs) has been found to have deviations such as a high fundamental frequency, elevated jitter and shimmer, and inadequate intonation. However, two important dimensions of prosody (temporal and spectral) have not been systematically investigated. Given that, in general, the resolution in CI hearing is best for the temporal dimension and worst for the spectral dimension, we expected this hierarchy to be ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…Most studies use a spectral, temporal or intensity component to calculate intonation. This corresponds with, respectively, measuring differences in fundamental frequency, duration and intensity within the utterance (Davies & Goldberg, 2006;Fitzsimons et al, 2001;Ladd, 2008;Olivati et al, 2017;van de Velde et al, 2018). Hancock et al (2014) andGelfer andSchofield (2000) used an intonation shift to describe intonation.…”
Section: Measuring Intonation Patternsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies use a spectral, temporal or intensity component to calculate intonation. This corresponds with, respectively, measuring differences in fundamental frequency, duration and intensity within the utterance (Davies & Goldberg, 2006;Fitzsimons et al, 2001;Ladd, 2008;Olivati et al, 2017;van de Velde et al, 2018). Hancock et al (2014) andGelfer andSchofield (2000) used an intonation shift to describe intonation.…”
Section: Measuring Intonation Patternsmentioning
confidence: 99%
“…of the utterance as a whole. The script "Intonation and stress trajectory" (Corthals, 2019a;Van Borsel, Vandaele, & Corthals, 2013) was used to calculate this parameter.…”
Section: General Fundamental Frequency Range (Hz and Erb)mentioning
confidence: 99%
See 2 more Smart Citations
“…In one of the few studies on French-speaking children who had been implanted early, Farah and colleagues (2018) showed that these children acquired adult patterns of prosodic focus and phrasing at a hearing age of about 6 years, similar to children with TH of the same hearing age (for other results on prosody in French children with CI, see Le Normand & Lacheret, 2010). Van de Velde and colleagues (2018) conducted a study on the spontaneous speech produced by Dutch early and late implanted children recorded 18, 24 and 30 months after implantation. The authors took into account both temporal (i.e.…”
Section: Introductionmentioning
confidence: 99%